Histone Demethylases JMJ30 and JMJ32 Modulate the Speed of Vernalization Through the Activation of FLOWERING LOCUS C in Arabidopsis thaliana - Maruoka, Takashi; Gan, Eng-Seng; Otsuka, Nana; Shirakawa, Makoto; Ito, Toshiro (Frontiers in Plant Science, 2022)
Vernalization is the promotion of flowering after prolonged exposure to cold. In Arabidopsis thaliana, vernalization induces epigenetic silencing of the floral repressor gene FLOWERING LOCUS C (FLC). Among the repressive epigenetic marks, the trimethylation of lysine 27 on histone H3 proteins (H3K27me3) is a critical contributor to the epigenetic silencing of FLC. The deposition of H3K27me3 is mediated by Polycomb Repressive Complex 2 (PRC2). Conversely, the elimination of H3K27me3 is mediated by histone demethylases, Jumonji-C domain-containing protein JMJ30 and its homolog JMJ32. However, the role of JMJ30 and JMJ32 in vernalization is largely unknown. In this study, we found that cold treatment dramatically reduced the expression levels of JMJ30 and did not reduce those of JMJ32. Next, by using the genetic approach, we found that the flowering of jmj30 jmj32 was accelerated under moderate vernalized conditions. Under moderate vernalized conditions, the silencing of FLC occurred more quickly in jmj30 jmj32 than in the wild type. These results suggested that the histone demethylases JMJ30 and JMJ32 brake vernalization through the activation of FLC. Our study suggested that PRC2 and Jumonji histone demethylases act in an opposing manner to regulate flowering time via epigenetic modifications.